Composition and Evolution of Continental Crust at Orogenic Belts: Constraints From a 3‐D Crustal Model of Southeast China. Issue 12 (16th December 2022) - Sun, Yao; Gao, Ruohan; Li, Zhiwei; Wang, Andong; Han, Ran; Xi, Yufei; Liu, Jingao
Abstract: The chemical composition of continental crust is fundamental and crucial to understanding its origin and evolution. Orogenic belts make up about 30% of the global continental crust, yet their chemical compositions are still poorly constrained. In this study, we report an overall estimate for the continental crust composition of a collisional orogenic belt terrane: the Southeast China. The estimate is obtained through a 3‐D crustal model combining a lithology proportion model and probability density function models for element concentrations of various lithologies. Based on our model, the Southeast China crust is amongst one of the most evolved continental crust composition estimates (71.0% SiO2 content for the upper crust and 64.7% SiO2 for the bulk crust). A strong correlation between SiO2 and the chemical index of alteration (CIA) of different composition models for upper continental crust (UCC) indicates that chemical weathering is a controlling factor for the development of a felsic UCC. In contrast, weak correlations of SiO2 with Ninorm (15.9*Ni/Al2 O3 ) and CIA suggest that igneous differentiation and chemical weathering act together to modify the composition of the bulk continental crust. Orogenic belt terranes like the Southeast China can develop a highly evolved crustal composition, especially for the upper crust, due to extensive intracrustal reworking and differentiation, enhanced chemical weathering, and potential subsequent delamination and removal of thickened crust root. Therefore, an overall estimation of the average composition of continental crust should take into account the more evolved composition of orogenic belts. Plain Language Summary: The chemical composition of continental crust is the foundation for better understanding its formation and evolution. Despite many estimations on the composition of Precambrian continental crust, there are less studies on Phanerozoic orogenic belts which make up 30% of the global continental crust. This study provides an estimate of the crustal composition of the Southeast China orogenic terrane. The results are obtained by constructing a crustal model combining geologic, geophysical, and geochemical data. We find that the Southeast China almost has the most evolved upper and bulk crust composition compared with other crustal composition estimations. We suggest that chemical weathering is the most important process to modify upper continental crust composition, whereas the composition of bulk continental crust is controlled by both intracrustal differentiation and chemical weathering. Hence, orogenic belts can develop highly evolved crustal compositions as the result of extensive intracrustal reworking coupled with enhanced chemical weathering and potential removal of thickened crust root. An overall estimation of the average composition of continental crust should take this into account. Key Points: A crustal model of SE China combining geologic, geophysical, and geochemical data is built to estimate the composition of orogenic belts Orogenic belts develop highly evolved composition by extensive intracrustal reworking, enhanced chemical weathering, and crust delamination An overall estimation of the average composition of the continental crust should take the composition of orogenic belts into account